Removal Of Total Coliform, E. Coli, UV254, Particles, Total Dissolved Solids (TDS), Suspended Solids (SS), And Colour Using Zeolite And Activated Carbon Mixture In Riverbank Filtration - Lee, Weoi Jye (Universiti Sains Malaysia, 2018)
Urbanization together with the exponential growth of human population causes serious water pollution. In 2006, the Department of Environment (DOE) registered 18,956 water pollution point sources comprising mainly sewage treatment plants (9,060 : 47.79% inclusive of 601 Network Pump Stations), manufacturing industries (8,543 : 45.07%), animal farms (869 : 4.58%) and agro-based industries (484 : 2.55%). Poor water quality of rivers and lakes, flooding and water shortage have become major issues in Malaysia. To tackle the problem, Malaysia has started to use river bank filtration (RBF) for water abstraction. Zeolite and activated carbon as composite adsorbent has the potential to enhance the RBF system. Therefore, this study was investigated to look at possibility of using both materials in the RBF system. Both materials were first determined using scanning electron microscopy (SEM) and X-ray fluorescence method. The filter column that resembles RBF system was then designed. The filtration rate that are appropriate for RBF system was pre-determined. The removing performance of particles, total coliform, E. coli, total dissolved solids (TDS), suspended solids (SS), UV254 and colour was then determined at different configurations as follows: using different arrangements of zeolite and activated carbon with size from 1.18 mm to 2.0 mm, 1) mixed arrangement; 2) and two distinctive layers of zeolite (bottom) and activated carbon (top). The SEM results shown that the zeolite consists of micron-size crystal with small size of pores. Through XRF test, it can be concluded that the zeolite was from clinoptilolite group with main constituents of SiO2 (79%) and Al2O3 (13%). For activated carbon, SEM results show that it is highly amorphous and has layered-like structures with the presence of cavities. XRF tests for activated carbon shows that its main constituents are C (93%) and SiO2 (4%) with few transition elements (Fe, Zn and Cu) as catalyst within their compounds. Filtration experiments done at flow rate of 18.3 cm3/min and retention time of 30 minutes have shown good removal performance for almost all the parameters except TDS and particle sizes. Removal of total coliform and E. coli were excellent with 95% and 99% removal, respectively. It is then followed by 67% to 84% removal efficiency for turbidity, 45% to 70% for colour and 20% to 47% for UV254. Zeolite and activated which are alkaline in nature had caused the increase in pH of water after filtration. Column A which consists of a mixture of zeolite and activated carbon, performed better in removing suspended solids, colour and turbidity whereas for column B which has two distinctive layers of zeolite and activated carbon, performed better in removing total coliform, E. coli, and UV254. It has been observed that the pollutants filled up the pores of zeolite and activated carbon after filtration. However, concentration of particles and total dissolved solids (TDS) could not be determined due to leaching effect of zeolite and activated carbon into the water.